Marcadores Tumorales En El Cáncer De Mama Y Próstata En Caninos - Revisión De Literatura Científica 2010 Al 2021” - Murillo Anaya, María Fernanda (Universidad Antonio Nariño, 2023)
Tumor markers are molecules that are mostly presented as glycoproteins, these could be elevated in the presence of a neoplasia, as a reaction of the individual towards the tumor or as a product of the tumor itself, these molecules can find them in different biological fluids.